Empowerment of cake SMEs in Laras Village through profit optimization - Mardiningsih; Putri Khairiah Nasution; Enita Dewi Br Tarigan; Maulida Yanti (Journal of Saintech Transfer, 2025)
In a village, called Laras, there is a small business (SME) that produces wet and dry cookies, marketed on a small scale. The problems faced by the SMEs include the lack of a strategic and easily accessible stall for the public, as well as minimal product promotion being conducted. Several important indicators in optimizing product sales results can be achieved through packaging design, shelf availability, and effective marketing. To address these issues, the Community Service Team provided a workshop to enhance skills related to the making of packaging label and marketing techniques. The abdimas team also provided an attractive shelving unit as a place to display the cakes to facilitate sales and make them visible to the surrounding community. In the end, a paired t-test was used to measure the benefits of the service provided. Based on the questionnaire data, the t-test statistic value obtained is |-65.21| = 65.21 > t-table value 1.699, hence it can be concluded that there was an improvement outcome after the service was conducted.